Depression, anxiety, stress and behavioral response related to COVID-19 pandemic among general population - Saud, Mithu; Timalsina, Punjita; Tiwari, Durga; Shrestha, Shova (Journal of Chitwan Medical College, 2021)
Background: Since the December 2019, a novel corona virus disease (COVID-19) first identified in China, spreading around the world and infected millions of people. This pandemic has severely affected the socio-economic and mental health status of people due to lockdown and great uncertainty of elimination of the virus. This study aim to identify the depression, anxiety, stress and behavioral response related to COVID-19 pandemic among general population of Kathmandu Valley. Methods: A descriptive cross sectional study carried out using convenient sampling duringCOVID-19 Pandemic. Data was collected by using structured standard DASS 21 scale. The SPSS version 22 was used to analyze data. Results: There were total 411 general people participated, among them 25.3%, 22.9%, and 11.9% had mild to extreme severe level of depression, anxiety and stress respectively were prevalent. There is a statistical significant association between marital status, educational level and level of depression at 95% confidence level (p value< 0.05). Majority of respondents had change their behavior as maintaining hand hygiene, wore a mask and had limited physical contact with people. There is a statistical significant between age, gender and level of education with recently avoiding smoking and drinking related behavior. Conclusions: This study concludes that the general population had depression, anxiety and stress because of the fear of getting infection; people were more likely change their behavior to prevent the risk of infection. This study suggests addressing the need of mental health services such as counseling, hotline services and desk by the stakeholders to promote mental wellbeing of people.